TENDON CONTRACTURE IN CATTLE - da Silva, Elen Luana; da Silva, Luiza Helena; Gervasi, Amabile Vitoria; Melo, Lailla Gabriela Brito; da Cunha, Ana Luiza Caldeira; Vieira, Bianca; Negherbon, Anabell; Lopes, Izaú Cardoso; Diniz, Lucas Nascimento; Casas, Bruno Alexandre Dombroski; Schwegler, Elizabeth (Seven Editora, 2026)
Flexor tendon contracture is one of the most frequent congenital conditions in calves, with an etiology that is not yet fully elucidated, compromising locomotion and animal welfare. The objective is to describe the classification, diagnosis, and therapeutic approaches to this condition, with emphasis on the surgical technique. To this end, the condition is described, based on data from the literature and the structuring of clinical and surgical procedures. The severity of the condition varies according to the degree of weight-bearing on the limb(s) and the animal’s standing ability, being diagnosed by clinical and complementary examination. Treatment ranges from conservative management with physiotherapy in mild cases, the use of anti-inflammatory drugs and tetracycline antibiotics in moderate cases, to surgical interventions by tenotomy in severe conditions. Thus, the therapeutic choice depends on the clinical manifestation, which allows us to conclude that early diagnosis combined with appropriate intervention are fundamental for correction and better prognosis, avoiding permanent sequelae.